Real-world study of pegylated interferon α-2a to treat mycosis fungoides/Sézary syndrome using time to next treatment as a measure of clinical benefit: an EORTC CLTG study - Mitsunaga, Keila; Bagot, Martine; Ram-Wolff, Caroline; Guenova, Emmanuella; von Gugelberg, Christina; Hodak, Emmilia; Amitay-Laish, Iris; Papadavid, Evangelia; Jonak, Constanze; Porkert, Stefanie; Scarisbrick, Julia; Applewaite, Rona; et al. (British journal of dermatology, 2024)
Mycosis fungoides (MF) and Sézary syndrome (SS) are chronic malignant diseases that typically necessitate diverse strategies to achieve remission. Systemic interferon (IFN)-α (subtypes 2a and 2b) has been used to treat MF/SS since 1984; however, its production was recently stopped. The recombinant pegylated (PEG) form of IFN-α-2a remains the only alternative IFN treatment, although it has not been approved for use in MF/SS.To assess the effectiveness and safety of PEG-IFN-α-2a in monotherapy and in combination with other treatments using time to next treatment (TTNT) as a measure of clinical therapeutic benefit in a real-world setting.We conducted an international, multicentre retrospective study of patients with MF and SS (of any stage) treated with PEG-IFN-α-2a from July 2012 to February 2022. Patients were included across 11 centres in 10 countries. The primary endpoints were to determine the TTNT of PEG-IFN-α-2a and adverse events (AEs) in MF/SS.In total, 105 patients were included [mean (SD) age 61 (13.1) years]; 42 (40.0%) had stage IA-IIA and 63 (60.0%) had stage IIB-IVB disease. PEG-IFN-α-2a was combined with other therapies in 67 (63.8%) patients, most commonly with extracorporeal photopheresis (36%) and bexarotene (22%). Patients with stage I-IIA disease achieved an overall response rate (ORR) of 57%; the ORR in those with stage IIB-IVB disease was 51%. Combination treatment resulted in a median TTNT of 10.4 months (range 0.6-50.7) vs. 7.0 months (range 0.7-52.4) for those who received monotherapy (P < 0.01). Overall, the mean (SD) TTNT was 9.2 (10.6) months and the ORR was 53.3% (n = 56). A complete response was seen in 13% of patients and a partial response in 40%. AEs were described in 68.6% (n = 72) of patients. Flu-like symptoms (n = 28; 26.7%), lymphopenia (n = 24; 22.9%) and elevated liver function (n = 10; 9.5%) were the most frequently reported. Grade 3-4 AEs were reported in 23 (21.9%) patients, mostly related to myelosuppression.PEG-IFN-α-2a for MF/SS resulted in an ORR of 53.3% and a mean (SD) TTNT of 9.2 (10.6) months. Combination regimens were superior to monotherapy and doses of 180 µg PEG-IFN-α-2a weekly were related to a higher ORR.Mycosis fungoides (MF) and Sézary syndrome (SS) are rare types of cancers of the lymphatic system (lymphomas). They result in patches, plaques and/or tumours on the skin that usually need a combination of treatments to be controlled. A drug called interferon alpha (IFN-α) has been used to treat cutaneous lymphomas since 1984, but its production was recently stopped, so another form of it called ‘recombinant pegylated IFN α-2a’ (PEG-IFN-α-2a) is the only alternative IFN treatment, even though it has not been formally approved for MF/SS. The lack of studies on PEG-IFN-α-2a for MF/SS treatment has meant that its use can vary between institutions.This study aimed to investigate the effectiveness, the safety and how well PEG-IFN-α-2a is tolerated as single treatment or in combination with other MF/SS treatments. We carried out a study of patients with MF/SS treated with PEG-IFN-α-2a between July 2012 and February 2022. In total, 105 patients were included from 10 countries. We found that 53% of the patients responded to PEG-IFN-α-2a treatment. We also found that doses of 180 µg weekly, as well as combining PEG-IFN-α-2a with other treatments, resulted in higher response rates and a longer time until a new treatment needed to be added. However, at least one adverse event occurred in 69% of patients. The most common were flu-like symptoms, a reduction in the number of white blood cells and increased liver function. Severe adverse events occurred in 21% of the patients, mostly related to a reduction in the number of blood cells.Overall, our study findings suggest that PEG-IFN-α-2a is an effective and generally well-tolerated option among the treatments for MF/SS, with patients experiencing a better response when it was used as part of a combination therapy and on doses of 180 µg weekly.
Online veröffentlicht: 10. April 2024
Gesehen am 16.01.2025